Is a Theory of Cyberspace Dominance Possible? An Assessment from the Perspective of China’s Cyber Sovereignty Approach - Aybala Lale Kahraman (Güvenlik Stratejileri Dergisi)
In today’s rapidly digitalizing world, cybersecurity requires the protection of information and communication technologies as well as the infrastructure of countries. In this framework, some countries consider cyber sovereignty to be connected with cybersecurity as an approach that discloses the control and authority of states over their digital infrastructures. This study analyzes the cybersecurity policies and understanding of cyber sovereignty in China. In doing so, the possibility of theorizing dominance in cyberspace is discussed. In this context, the main purpose of this study is to examine the theoretical dimensions of cybersecurity and cyber sovereignty concepts and to analyze China’s cybersecurity policies and cyber sovereignty approach. Cyberspace represents a new field of dominance in international relations. Rather than providing a definitive answer to whether cyber sovereignty is possible under international law, the focus should be on how cyber sovereignty can play a role in international power struggles and shape cybersecurity policies. In this context, the study’s methodology consists of a brief introduction to cybersecurity, followed by an analysis of the research question of whether cyberspace dominance is possible and the concept of cyber sovereignty. Within the scope of the theoretical framework, a literature review of the relevant concepts was conducted, and China’s cybersecurity policies and cyber sovereignty approach were analyzed as a case study. The documents, sources, and data discussed throughout the study demonstrate China’s understanding of cyber sovereignty and how it is shaped on international platforms. The study concludes that if China sees cyberspace sovereignty as the key to becoming a global power in the international system, it must integrate all factors, including military, political, and economic factors, besides cybersecurity.